Rosai-Dorfman Disease: Rare Pulmonary Involvement Mimicking Pulmonary Langerhans Cell Histiocytosis and Review of the Literature - Rashid AL Umairi; Danielle Blunt; Wedad Hana; Matthew Cheung; Anastasia Oikonomou (Case Reports in Radiology)
Rosai-Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy, is a rare nonmalignant lymphohistiocytic proliferative disorder. We report a patient with RDD who presented with multiple skin lesions, pulmonary involvement, and CT manifestations mimicking Langerhans cell histiocytosis, which improved after initiation of corticosteroid treatment.